Mengaudit Kualitas Kebijakan Pembangunan Indonesia: Sebuah Pendekatan Berbasis Hak Asasi Manusia (HAM) - Pihri Buhaerah (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2014)
This study aims to audit the quality of Indonesia's development policy in the light of human rights (HAM). The audit is needed to get a full picture of the fulfillment of human rights situation in Indonesia in development. Analytical tools used to audit the quality of Indonesia's development are some key concepts in the international Covenant on ESC rights such as the maximum available resources, progressive realization, non-retrogression, and minimum core obligations. The method used in this study is a descriptive analysis and rely on secondary data through the study of literature to the works previously published research, books, journals, and official statistics from government and international agencies. Overall, the performance of Indonesia's development policy can be said to be still less qualified. The study results also show that the results do not show development maximum available resources, progressive realization, non-retrogression, and the fulfillment of minimum core obligations. As a result, the quality level of social welfare has not improved in spite of the political budget for social development from time to time.